Outcomes of referrals by community optometrists to a hospital glaucoma service. Issue 9 (19th August 2005) - Bowling, B; Chen, S D M; Salmon, J F
Abstract : Aim: To determine the outcomes resulting from optometric referrals to a specialist glaucoma screening clinic over a 10 year period. Methods: Details of the initial clinical assessment of all new patients referred to the adult glaucoma screening clinic at Oxford Eye Hospital were collected prospectively from July 1994 to June 2004. Results: Optometrists working in community practice initiated 2505 referrals. Of these, glaucoma was confirmed in 510 patients (20.4%), including 160 with normal intraocular pressure (IOP). A diagnosis of ocular hypertension was made in 747 patients (29.8% of referrals) and 125 (5.0%) were categorised as glaucoma suspects. There was no evidence of a diagnostic trend over the period of data collection. Treatment to lower IOP was commenced in 458 patients (18.3%). Nearly half of those referred, 1148 (45.8%), were discharged from ophthalmological review at the first visit. Conclusion: In this survey, the largest of its nature, only one in five subjects had glaucoma and nearly half were discharged from hospital ophthalmological review. The findings provide a baseline against which the effectiveness of any future system of glaucoma detection in the United Kingdom can be compared.